2012
DOI: 10.5194/acp-12-6999-2012
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of black carbon aging in the OsloCTM2 and implications for regional transport to the Arctic

Abstract: Abstract.A critical parameter for the atmospheric lifetime of black carbon (BC) aerosols, and hence for the range over which the particles can be transported, is the aging time, i.e. the time before the aerosols become available for removal by wet deposition. This study compares two different parameterizations of BC aging in the chemistry transport model OsloCTM2: (i) A bulk parameterization (BULK) where aging is represented by a constant transfer to hydrophilic mode and (ii) a microphysical module (M7) where … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 87 publications
5
20
0
Order By: Relevance
“…Indeed, changes in a model's aerosol scheme (i.e., treatment of microphysical properties and atmospheric removal of BC) can change simulated concentrations by more than an order of magnitude in remote regions such as the Arctic (Vignati et al, 2010). Implementing a more realistic aerosol microphysical scheme in one model increased the Arctic BC concentrations near the surface in winter, which is in better agreement with the observations, but at the same time it exacerbated the model overestimates at higher altitudes (Lund and Berntsen, 2012). Another study attributed the transition from high wintertime aerosol concentrations to low concentrations in the summer to the transition from ice-phase cloud scavenging to more efficient warm cloud scavenging, further amplified by the appearance of warm drizzling cloud in the late spring and summer boundary layer (Browse et al, 2012).…”
Section: Introductionsupporting
confidence: 78%
“…Indeed, changes in a model's aerosol scheme (i.e., treatment of microphysical properties and atmospheric removal of BC) can change simulated concentrations by more than an order of magnitude in remote regions such as the Arctic (Vignati et al, 2010). Implementing a more realistic aerosol microphysical scheme in one model increased the Arctic BC concentrations near the surface in winter, which is in better agreement with the observations, but at the same time it exacerbated the model overestimates at higher altitudes (Lund and Berntsen, 2012). Another study attributed the transition from high wintertime aerosol concentrations to low concentrations in the summer to the transition from ice-phase cloud scavenging to more efficient warm cloud scavenging, further amplified by the appearance of warm drizzling cloud in the late spring and summer boundary layer (Browse et al, 2012).…”
Section: Introductionsupporting
confidence: 78%
“…Lack of understanding of pollutant deposition rates may be a key driver for the poor skill of many models in simulating the seasonal cycle and magnitude of aerosol pollutants when compared to Arctic measurements (AMAP, 2015;Eckhardt et al, 2015). In particular, disagreement with observations has been shown to be sensitive to the representation of wet scavenging and aerosol microphysical (e.g., black carbon aging) processes in models (e.g., Browse et al, 2012;Garrett et al, 2011;Liu et al, 2011;Lund and Berntsen, 2012). More recently, a model simulation using observed meteorology to reasonably simulate the seasonal cycle and vertical distribution of pollutants in the Arctic in the year 2008 found that aerosol wet scavenging was ∼3 times larger than dry scavenging in the Arctic (Breider et al, 2014).…”
Section: Processing Fate and Impacts Of Arctic Pollution On Climate mentioning
confidence: 99%
“…Koch et al (2009) evaluated Arctic atmospheric BC in AeroCom phase I models and found that increasing BC lifetime, which is accomplished by decreasing the aging rate or by reducing removal by ice clouds, has a large impact on BC surface concentrations in remote regions. Analysis of surface measurements at Barrow, Alaska, indicates that the seasonal cycle of "Arctic haze" is dominated by wet scavenging rather than efficiency of transport pathways from source regions (Garrett et al, 2010;Browse et al, 2012;Lund and Berntsen, 2012;Wang et al, 2013). Liu et al (2011) concluded that the simulation of BC in the Arctic is significantly improved by using a parameterization of BC aging rate that is proportional to the OH radical concentration, reducing dry deposition velocities over ice and snow, and decreasing ice cloud wet removal efficiency.…”
Section: Inter-model Deposition Variabilitymentioning
confidence: 99%